2012
DOI: 10.1101/cshperspect.a006221
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Biomarkers in Alzheimer Disease

Abstract: Research progress has provided detailed understanding of the molecular pathogenesis of Alzheimer disease (AD). This knowledge has been translated into new drug candidates with putative disease-modifying effects, which are now being tested in clinical trials. The promise of effective therapy has created a great need for biomarkers able to detect AD in the predementia phase, because drugs will probably be effective only if neurodegeneration is not too advanced. In this chapter, cerebrospinal fluid (CSF) and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 169 publications
(191 reference statements)
2
151
0
6
Order By: Relevance
“…They may be employed for the in vitro monitoring of drug discovery plans intended to identify new molecules inhibiting amyloidogenic mechanisms and to provide surrogate measures assessing treatment efficacy of novel Ab-targeting drugs, which would decrease the time and cut the costs of clinical trials [94]. In addition, biomarkers may help demonstrate the usefulness of a certain therapy in a specific patient, thus assisting the physician to find the proper medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may be employed for the in vitro monitoring of drug discovery plans intended to identify new molecules inhibiting amyloidogenic mechanisms and to provide surrogate measures assessing treatment efficacy of novel Ab-targeting drugs, which would decrease the time and cut the costs of clinical trials [94]. In addition, biomarkers may help demonstrate the usefulness of a certain therapy in a specific patient, thus assisting the physician to find the proper medication.…”
Section: Discussionmentioning
confidence: 99%
“…As emphasized by Blennow et al (2012) [94], given that the diagnostic accuracy for the combination of CSF Ab 1-42 , t-tau, and p-tau has been reported to be higher than for any biomarker alone [76,93,95,96], a multiparameter assay, utilizing the Luminex TM xMAP technology (Luminex Corporation, Austin, TX, USA) to enable simultaneous quantification of these CSF biomarkers, has been developed [97]. The employment of this assay in multicenter studies on CSF biomarkers has yielded a good diagnostic performance [75,76,79,98].…”
Section: Progression From MCI To Admentioning
confidence: 99%
“…One reason is that Tau is elevated in the cerebrospinal fluid (CSF) at an early stage of AD and therefore serves as a biomarker (Hampel et al 2010;Blennow et al 2011). The origin of CSF-Tau is not clear, but dying and disintegrating neurons could contribute to it.…”
Section: Tau Protein In Neurofibrillary Degenerationmentioning
confidence: 99%
“…Despite substantial progress has been made in the area of biomarker development to confirm the diagnosis at early-clinical AD stages, less is known about the potential role of biomarkers in peripheral tissues in the prediction of AD [58]. Since it has been demonstrated for decades the existence of biochemical changes in the brain preceding the clinical AD onset (up to 20 years in advance) [59,60] it is suggested that these changes may be also indirectly reflected in biological fluids.…”
Section: Biomarkers In Peripheral Tissuesmentioning
confidence: 99%